2013
DOI: 10.1039/c3ra40447a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a ZnO nanogenerator for eco-friendly biomechanical energy harvesting

Abstract: We present a new device structure for effective energy harvesting from human body movement using a ZnO nanogenerator. This is the first report on both piezoelectric and triboelectric effects in the same device. The fabricated device structure consists of a double-sided ZnO nanowire array sandwiched between gold coated ZnO nanowire arrays using polydimethylsiloxane. The peak open circuit voltage (V oc ) and short circuit current (I sc ) were recorded as 30 V and 300 nA respectively with power density of 0.390 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 40 publications
0
69
0
Order By: Relevance
“…[1][2][3][4] Taking the forms of irregular air flow/vibration, ultrasonic waves, body movement, and hydraulic pressure, mechanical energy is ubiquitously available in our living environment. [1][2][3][4] Taking the forms of irregular air flow/vibration, ultrasonic waves, body movement, and hydraulic pressure, mechanical energy is ubiquitously available in our living environment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Taking the forms of irregular air flow/vibration, ultrasonic waves, body movement, and hydraulic pressure, mechanical energy is ubiquitously available in our living environment. [1][2][3][4] Taking the forms of irregular air flow/vibration, ultrasonic waves, body movement, and hydraulic pressure, mechanical energy is ubiquitously available in our living environment.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Among the conversion methods, nanogenerator is an effective device tool to harvest the low frequency mechanical energy through piezoelectric and tribo-electrification processes. [9][10][11][12][13][14][15] On the other hand, the electrochemical capacitors (ECs) or supercapacitors are considered to be one of the most important next-generation energy storage devices, mainly due to their high power density, fast charge-discharge rates and long life times than rechargeable batteries and conventional dielectric capacitors. [16][17][18][19] Such a device can be used as a primary power storage source or auxiliary power storage source with rechargeable batteries in electric vehicles and other electronic devices for the purpose of power enhancement.…”
mentioning
confidence: 99%
“…These studies shown such energy sources to successfully power liquid crystal displays (LCDs), light-emitting diodes (LEDs), implantable biosensors, and many portable personal electronic devices [10]. Various nanostructured materials, such as ZnO [11][12][13], GaN [14], lead zirconium titanate (PZT) [15,16], BaTiO 3 (BTO) [17], NaNbO 3 [18], (1-x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PMN-PT) [19], ZnSnO 3 [20], polyvinylidene fluoride (PVDF) [9], and polytetrafluoroethylene (PTFE) [21] have been widely used for nanogenerator fabrication in a variety of forms, such as micro/nanowires, nanobelts and particles. Among them, ZnO is lead-free, biocompatible and has piezo and semiconducting properties [22,23]; its noncentrosymmetric nature has proven to be advantageous for nanogenerator applications.…”
Section: Introductionmentioning
confidence: 99%